Academic logic and corporate entrepreneurial intentions: A study of the interaction between cognitive and institutional factors in new firms. (August 2016) - Fini, Riccardo; Toschi, Laura
This article studies the extent to which corporate entrepreneurial intentions are enacted differently by academic and non-academic entrepreneurs. Using constructs from cognitive research and exploiting the theory of institutional logics, we observe that academic entrepreneurs, notwithstanding their engagement in entrepreneurship, still implement their corporate entrepreneurial intentions acting in accordance with the academic institutional environment to which they belong. Using a matched-pairs research design, our results show that academic entrepreneurs (compared to non-academic ones) leverage their awareness of technical competencies significantly more and their entrepreneurial self-efficacy and awareness of managerial skills considerably less. We discuss the theoretical and managerial implications related to how cognitive and institutional factors interact to foster entrepreneurial value in newly established firms.